Business Process Maturity Model Used to Assess the Admissions Management of SMP Telkom Purwokerto - Wulandari, Astri; Marcelino, Dandy (Jurnal Pendidikan Progresif, 2023)
Objective: The purpose of this study is to evaluate the development of Telkom Purwokerto middle school's new student admissions management procedure. Method: This study adopts a descriptive method, which aims to accurately portray the current state of the phenomena or situation under investigation. The Organizational Process Management (OPM) process area from the Business Process Maturity Model (BPMM) is employed at the third maturity level in this study. The interview yields a score between 0 and 5 that represents the Vocational School's assessment of how far along in the process the candidate is. Finding: This success yields a discrepancy for each inquiry, with the goal of gauging how well OPM Level 3 maturity is met and pinpointing where improvements may be made. Overall, the PPDB process has not yet reached the OPM-Level 3 maturity level due to the presence of practices that have not been implemented or have not yet reached the stage of continuous improvement. Conclusion: Therefore, the need to establish and implement the process consistently to move towards continuous improvement is a necessary suggestion for enhancement. Keywords: new student admission, the maturity model for business processes, third-level maturity, management of organizational procedures.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202316